Power Transfer Capability & Reliability Improvement in a Transmission Line using Distributed Power- Flow Controller - P. Ramesh; M. Damodara Reddy (Institute of Advanced Engineering and Science, 2012)
The Distributed Power Flow Controller (DPFC) is derived from the Unified power-flow controller (UPFC).The DPFC is a solution to control the power flow in a single transmission line. By eliminating the common DC link and distributing the three phase series converters of the UPFC, a new concept of the Distributed Power Flow Controller (DPFC) is achieved. The active power exchange between the two converters, which is through the common dc link in the UPFC, is now through the transmission lines at the third-harmonic frequency in the DPFC. It inherits the advantages of the UPFC and the DFACTS concept, which allow power flow control for multi-line systems with relatively low cost and high reliability without additional cost. This paper presents two types of DPFCs; one is one three phase shunt converter and four three phase series converters. Another model is one three phase shunt converter and nine single phase series converters. By using three phase series converters, no common dc link between shunt and series converters but cost will increases. By using single phase series converters, no common dc link between shunt and series converters and cost also decreases. Detailed simulations are carried out on two- machine systems to illustrate the control features of these devices and their influence to increase power transfer capability and every series converter consists of D-FACTS concept so Reliability also improves because failure of series converters does not effect.DOI:http://dx.doi.org/10.11591/ijece.v2i4.357